Problemas de recogida y fijación de muestras del discurso digital - Vela Delfa, Cristina (2015)
One of the challenges faced by the analyst of digital communication consists on the estab-lishment of a corpus that preserve the representativeness and which responds to the nature of these samples of language, in particular as regards two parameters: multimodality and the multi-simultaneity. The article has three objectives. On the one hand, we review the sit-uation of samples of digital speech at international level and specifically for the Spanish. Then, we show a methodological reflection on the problems of collecting and setting of da-ta in the digital speech, from four cornerstones (communicative situation, nature of the data, representativeness of the sample and ethical issues). Finally, we propose guidelines to col-lect and transcript samples of digital speech for the repository feed; textual or enriched with multimodal data to the repository code.